jjkjg
subjects
3 tháng 2 lúc 14:39

câu a

\(x-\dfrac{1}{2}=\dfrac{7}{13}\cdot\dfrac{13}{28}\\ x-\dfrac{1}{2}=\dfrac{1}{4}\\ x=\dfrac{1}{4}+\dfrac{1}{2}\\ x=\dfrac{3}{4}\)

câu b

\(x\div\dfrac{15}{11}=-\dfrac{3}{12}\div8\\ x\div\dfrac{15}{11}=\dfrac{-1}{32}\\ x=-\dfrac{1}{32}\cdot\dfrac{15}{11}\\ x=-\dfrac{15}{352}\)

câu c

\(\left(2x+\dfrac{3}{8}\right)\cdot\dfrac{7}{4}=-\dfrac{21}{32}\\ 2x+\dfrac{3}{8}=-\dfrac{21}{32}\div\dfrac{7}{4}\\ 2x+\dfrac{3}{8}=-\dfrac{3}{8}\\ 2x=-\dfrac{3}{4}\\ x=-\dfrac{3}{4}\div2\\ x=-\dfrac{3}{8}\)

câu d

\(x^2+\dfrac{9}{-25}=\dfrac{2}{5}\div\dfrac{5}{8}\\ x^2+\dfrac{-9}{25}=\dfrac{16}{25}\\ x^2=\dfrac{16}{25}-\dfrac{-9}{25}\\ x^2=1\\ \Rightarrow x=1\)

Bình luận (0)
Kiều Vũ Linh
3 tháng 2 lúc 14:41

d) \(x^2+\dfrac{9}{-25}=\dfrac{2}{5}:\dfrac{5}{8}\)

\(x^2-\dfrac{9}{25}=\dfrac{16}{25}\)

\(x^2=\dfrac{16}{25}+\dfrac{9}{25}\)

\(x^2=1\)

\(\Rightarrow x=-1;x=1\)

Bình luận (0)
Kiều Vũ Linh
3 tháng 2 lúc 14:42

Câu a, b, c bạn subjects giải đúng rồi. Sai câu d

Bình luận (0)

Các câu hỏi tương tự
Đỗ Thị Trà My
Xem chi tiết
dragon
Xem chi tiết
Nguyễn Tuấn Anh
Xem chi tiết
Nguyễn Thùy Anh
Xem chi tiết
TRẦN ĐỨC NGUYÊN
Xem chi tiết
Phạm Liêm
Xem chi tiết
Trần Quỳnh Như
Xem chi tiết
Xem chi tiết
Vũ Thu Hiền
Xem chi tiết
Minh Đăng
Xem chi tiết